The Influence Of Bioinformatics In The Study Of Influenza Virus - Nadia Br Sembiring; M.Rizky Ramadhan; Salsabila Yusra; Afthar Kautsar; Muhammad Iqbal (SEAN Institute, 2024)
Bioinformatics plays an increasingly important role in the study of influenza viruses, especially in understanding genetic evolution, drug resistance, and developing more effective therapies. This study aims to explore the application of bioinformatics in analyzing genomic data of influenza viruses, designing drugs and vaccines, and monitoring the spread of virus variants. The research method uses a quantitative approach with secondary data analysis in the form of genome sequencing results and resistance data from various influenza virus isolates . Normality , validity, and reliability tests are carried out to ensure data quality, while bioinformatics analysis is applied to identify genetic mutations, protein structures, and virus spread patterns. The results show that genomic data analyzed with bioinformatics allows the identification of mutations that affect drug resistance, geographic mapping of resistant variants , and prediction of potential mutations in the future. In addition, bioinformatics contributes significantly to the design of more specific vaccines by utilizing viral epitope analysis . In conclusion, bioinformatics has a major impact on the development of more effective influenza control strategies, both in terms of therapy and prevention, as well as accelerating the response to future pandemic threats